Prototipo de humedal artificial como sistema complementario a una PTAR (2022)
The contamination of water bodies has increased in recent years due to the lack of wastewater treatment plants due to their high cost of construction, operation and maintenance. Failure to treat this wastewater is harmful to the animals that inhabit the bodies of water that receive them, since they can ingest contaminants. This can later cause diseases in the people who live near the water currents since sometimes they They feed on the fish that remain in these channels. Due to the above, it is important the search for cheaper systems, easier to operate and, above all, affordable for communities in general. Based on previous experiences, the construction of a prototype of artificial wetland that allows to improve the quality of the water before being discharged into the rivers and that can even be used for irrigation of crops and for the consumption of animals.For the development of this research project, several species of plants from wetlands and different substrates, which together with microorganisms work in consortium forming a symbiosis, allowing the reduction and degradation of wastewater contaminants. Constructed wetlands use organic components that have a low cost in the market which decreases the value in the implementation, maintenance and commissioning gear, which, compared to conventional systems, minimizes the impact on the environment environment (2009, Romero et al). The applied methodology consisted of building and implementing a wetland prototype with synthetic water that simulated domestic wastewater. This water had previously established components that allowed it to be classified as water residual. Following this, it was evaluated if the retention times are adequate to obtain a sufficient reduction of contaminants and that this water at the end of the process can be reused for field activities. 8 Based on the development of the research project and being aware of what entails the maintenance of the artificial wetland, the biggest challenge we faced exposed is the adaptation of plants to the artificial environment. When working with beings alive we run the risk that plants will not survive and thrive in the new environment that has been arranged for them, so it was necessary to also evaluate their individual growth, the height of the foliage, the number of leaves, the physical appearance and the other parameters that allow us to identify the physical and food needs necessary for a good performance in terms of the degradation of contaminants present in the water synthetic.